Cyperotundone promotes chemosensitivity of breast cancer via SRSF1 - Li, Chao; Wang, Lin; Liu, Zhaoyun; Wang, Xinzhao; Sun, Luhao; Song, Xiang; Yu, Zhiyong (Frontiers in Pharmacology, 2025)
Breast cancer is among the most common malignancies and the leading cause of cancer-related deaths in women. SRSF1 proteins belong to an important splicing factor (SF) family and bind to different splicing regulatory elements (SREs) to promote or inhibit splicing, such as oncogenic splice-switching of PTpMT1, which promoting the progression of cancer. Cyperotundone (CYT) is the major bioactive component of sedge and reported to exhibit multiple biological functions, including its potent cytotoxic effect on breast cancer cells. However, the detailed impact and molecular mechanisms of CYT in breast cancer remain poorly understood. This study aimed to investigate the effects of CYT on breast cancer drug resistance and to explore the molecular mechanisms. CYT significantly suppressed the in vitro and in vivo growth of BC cells without affecting the normal cells at different doses (P < 0.001), induced cell apoptosis, and inhibited the migration and invasion of drug-resistant BC. In comparison with the mono treatment with CYT, combination of CYT and doxorubicin (Dox) enhanced the effects. CYT treatment regulated the RNA and protein levels of epithelial mesenchymal transition (EMT) biomarkers, suppressed the sphere formation ability and expression of cancer stem cell biomarkers in drug resistant BC cells. Results from transcriptome sequencing analysis and experiments identified significantly decreased SRSF1 level in drug resistant cells after CYT treatment. RNA and protein levels of SRSF1 and MYO1B were higher in drug resistant BC cells (P < 0.01). SRSF1 regulated alternative splicing of MYO1B to enhance the ability of drug resistance. Knockdown of SRSF1 significantly decreased expression of full-length MYO1B protein in drug-resistant BC cells (P < 0.05). Overexpression of SRSF1 and MYO1B revered the inhibitory effects of CYT. In conclusion, CYT repressed the growth and metastasis of BC cells and recovered drug sensitivity, through SRSF1-regulated the alternative splicing of MYO1B RNAs, which may represent a novel molecular mechanism to overcome drug resistance in breast cancer. Targeting SRSF1 or MYO1B may be identified as a novel molecular mechanism to against drug resistant in breast cancer.